2022
DOI: 10.1088/2053-1583/ac8e16
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature CVD growth of WSe2 enabled by moisture-assisted defects in the precursor powder

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have been proposed for a wide variety of applications, such as neuromorphic computing, flexible field effect transistors, photonics, and solar cells, among others. However, for most of these applications to be feasible, it is necessary to integrate these materials with the current existing silicon technology. Although chemical vapor deposition (CVD) is a promising method for the growth of high-quality and large-area TMD crystals, the high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Chen et al reported the direct synthesis of semiconducting PtSe2 layers at 450 • C [1016] and metallic PdSe2 layer at 300 • C [1017] on SOI to fabricate phototransistors, in which the top Si layer and the 2D layers as photoactive channel and the gate bias was applied to the bottom Si layer of the SOI. In addition, other 2D materials such as WSe2 [1018], SnS2 [1019], PdS2 [1020], PdSe2 [1021], and more have also achieved low-temperature growth compatible with BEOL through various methods. It is worth noting that besides the transfer and synthesis processes, other operations for integrating 2D materials with silicon also need to meet BEOL compatibility conditions.…”
Section: Heterogeneous Integration With Siliconmentioning
confidence: 99%
“…Chen et al reported the direct synthesis of semiconducting PtSe2 layers at 450 • C [1016] and metallic PdSe2 layer at 300 • C [1017] on SOI to fabricate phototransistors, in which the top Si layer and the 2D layers as photoactive channel and the gate bias was applied to the bottom Si layer of the SOI. In addition, other 2D materials such as WSe2 [1018], SnS2 [1019], PdS2 [1020], PdSe2 [1021], and more have also achieved low-temperature growth compatible with BEOL through various methods. It is worth noting that besides the transfer and synthesis processes, other operations for integrating 2D materials with silicon also need to meet BEOL compatibility conditions.…”
Section: Heterogeneous Integration With Siliconmentioning
confidence: 99%
“…Sassi et al [233] demonstrate the possibility of the low-temperature growth of WSe 2 using moisture-assisted defective WO 3 precursor powders. Through DFT calculations, the mechanism by which moisture promotes defect formation on the precursor crystal structure, leading to the reduction in the growth temperature, is elucidated.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…The typically required temperature is too high for BEOL integration, which requires temperatures in the 400 °C to 500 °C range. Some recent studies have worked to reduce the temperature, achieving minimal gains and managing to grow MoS 2 films at 560 °C for 50 min [ 169 ] or WSe 2 at 550 °C [ 170 ], albeit with slight modification to the typical CVD method.…”
Section: Fabrication and Working Principle Of 2d-material-based Gas S...mentioning
confidence: 99%